1999
DOI: 10.1034/j.1399-3054.1999.105201.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon fixation in Pinus halepensis submitted to ozone. Opposite response of ribulose‐1,5‐bisphosphate carboxylase/oxygenase and phosphoenolpyruvate carboxylase

Abstract: The effects of ozone exposure on carbon‐fixation‐related processes in Pinus halepensis Mill. needles were assessed over 3 months under controlled conditions. Ozone fumigation (200 ppb) did not induce a modification of either net CO2 assimilation or stomatal conductance in 1‐year‐old needles, whereas ribulose‐1,5‐bisphosphate carboxylase/oxygenase (Rubisco, EC 4.1.1.39) activity was shown to be reduced by a half. Moreover, this ozone‐induced reduction in Rubisco activity was associated with a decrease in the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 40 publications
3
33
0
Order By: Relevance
“…As a result, the apparent specific activity of Rubisco (k cat ) remained on the same level as in the chamber control (clone 80) or even increased (clone 4) under +O 3 . As the quantity of total soluble protein did not decrease, as also noted earlier (Fontaine et al 1999), stress proteins were probably synthesized instead of Rubisco (Pääkkönen et al 1998a). In both clones the increased mesophyll diffusion resistance r md contrib-uted to the reduction of photosynthesis under +O 3 , although less significantly in clone 4.…”
Section: The Influence Of Elevated O 3 On Leaf Photosynthetic Parametersmentioning
confidence: 58%
“…As a result, the apparent specific activity of Rubisco (k cat ) remained on the same level as in the chamber control (clone 80) or even increased (clone 4) under +O 3 . As the quantity of total soluble protein did not decrease, as also noted earlier (Fontaine et al 1999), stress proteins were probably synthesized instead of Rubisco (Pääkkönen et al 1998a). In both clones the increased mesophyll diffusion resistance r md contrib-uted to the reduction of photosynthesis under +O 3 , although less significantly in clone 4.…”
Section: The Influence Of Elevated O 3 On Leaf Photosynthetic Parametersmentioning
confidence: 58%
“…1), we found a significant increase in the stomatal conductance of Pinus halepensis before and during the water stress period and a decrease at the end of experiment. In other O 3 studies on Pinus halepensis, the authors have found a decrease in the stomatal conductance, except in the case of Fontaine et al [13], who found the highest values in the one-year old needles (no significant difference). Several hypotheses have been presented to explain such an increase in gw.…”
Section: Discussionmentioning
confidence: 81%
“…The Rubisco activity was generally not [16]. However, in some other species decreased Rubisco activity and quantity is a more constant response to O 3 [12,33,38].…”
Section: Discussionmentioning
confidence: 99%
“…Catabolic pathways such as dark respiration, glycolysis and the pentose phosphate pathway have been reported to show increased activity under oxidative stress in some tree species [9,10,12,16,45].…”
Section: Introductionmentioning
confidence: 99%